2007
DOI: 10.1007/s00247-006-0402-0
|View full text |Cite
|
Sign up to set email alerts
|

Pleuropulmonary blastoma, a distinctive neoplasm of childhood: report of three cases

Abstract: Despite its rarity, PPB should be considered in the evaluation of cystic or solid masses in children with respiratory distress. Plain film radiography alone is unable to distinguish between PPB and cystic malformations. CT represents the gold standard, although MRI can show the imaging features of solid enhancing nodules inside fluid-filled cavities, a mass causing lung compression, mediastinal shift, frequent pleural effusion, and no chest wall invasion. No preoperative imaging can reliably differentiate betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Rhabdomyosarcoma, pleuropulmonary blastoma and bronchioalveolar carcinoma are major malignancies known to be associated with CCAM [5,6,13]. The youngest age when these malignancies has been reported is 13 months for rhabdomyosarcoma [6], 9 months for pleuropulmonary blastoma [14,15], and 6 months for bronchioalveolar carcinoma [5].…”
Section: Discussionmentioning
confidence: 99%
“…Rhabdomyosarcoma, pleuropulmonary blastoma and bronchioalveolar carcinoma are major malignancies known to be associated with CCAM [5,6,13]. The youngest age when these malignancies has been reported is 13 months for rhabdomyosarcoma [6], 9 months for pleuropulmonary blastoma [14,15], and 6 months for bronchioalveolar carcinoma [5].…”
Section: Discussionmentioning
confidence: 99%
“…These cell clusters resemble the mucogenic cells of gastrointestinal epithelium and have been implicated in the occurrence of bronchioloalveolar carcinoma described both in older patients with CCAM1 and in others who have had a CCAM1 removed in infancy [18][19][20][21] . Rhabdomyosarcoma and pleuropulmonary blastoma are yet other major malignancies known to be associated with CCAM [22][23][24] . The higher levels of cyclin D1 observed in cancer tissues may be due to its increased expression or to deregulated degradation [25] .…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Previous studies have shown that histopathological type, mediastinal or pleural involvement, and metastases were correlated to the outcomes. 4,7 In summary, PPB is an extremely rare disease and most present symptom mimic respiratory infection. PPB should be considered in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%